2018
DOI: 10.4414/smw.2018.14635
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of follicular lymphoma: an update

Abstract: Over the last few years, there have been many changes in the management of patients with follicular lymphoma, resulting in improvements in progression-free survival and quality of life. In addition to established regimens such as radiotherapy and immunochemotherapy, new treatment options are on the horizon. Furthermore, even the use of established chemotherapy agents has evolved, with new combinations moving to the forefront of the current treatment strategy. Nevertheless, there remains an unmet need for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 84 publications
0
18
1
Order By: Relevance
“…As mentioned at the start, the mainstay of therapy in FL still focusses on cytoreduction and control of the disease while (advanced) FL is considered to be incurable. Apart from a combination of CD20‐antibodies and chemotherapeutic agents, other substances aiming at signalling inhibition such as Bruton’s tyrosine kinase inhibitor ibrutinib, the BCL2 inhibitor venetoclax or the selective phosphatidylinositol‐3‐kinase (PI3K) inhibitor idealisib are currently being tested in several studies (Bargetzi et al , ; Cheah & Fowler, ). Further potential new treatment options linked to the emerging field of immunotherapy including PD1/PDL1 checkpoint inhibition and chimaeric antigen receptor therapy (CART) are still in early trial phases or even considered experimental in FL (Stenner & Renner, ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned at the start, the mainstay of therapy in FL still focusses on cytoreduction and control of the disease while (advanced) FL is considered to be incurable. Apart from a combination of CD20‐antibodies and chemotherapeutic agents, other substances aiming at signalling inhibition such as Bruton’s tyrosine kinase inhibitor ibrutinib, the BCL2 inhibitor venetoclax or the selective phosphatidylinositol‐3‐kinase (PI3K) inhibitor idealisib are currently being tested in several studies (Bargetzi et al , ; Cheah & Fowler, ). Further potential new treatment options linked to the emerging field of immunotherapy including PD1/PDL1 checkpoint inhibition and chimaeric antigen receptor therapy (CART) are still in early trial phases or even considered experimental in FL (Stenner & Renner, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Hans algorithm, CD10 positivity determines the GCB type, whereas the multiple myeloma oncogene 1 positive stain favors the non‐GCB type (Hans et al, ). FL and DLBCL differ in their clinical behavior and require different treatment strategies (Bargetzi et al, ). Therefore, obtaining a sufficient tissue sample with preserved architecture is critical for a correct differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with FL (stage II and above) have a relapse rate of approximately 20% [49]. Most patients with R/R disease can be salvaged with chemoimmunotherapy or radioimmunotherapy approaches [50,51]. Patients who relapse/progress within 24 months of the diagnosis (POD24) have worse outcomes compared to those who relapse later [52].…”
Section: Current Therapeutic Landscape For Lymphomamentioning
confidence: 99%
“…A recent Center for International Blood and Marrow Transplant Research (CIBMTR) study showed that those who experience early treatment failure (ETF) after front-line chemoimmunotherapy may benefit from auto-HCT within one year of treatment failure [53]. Although chemoimmunotherapy regimens with fewer toxic effects have shifted the clinical focus away from auto-HCT as a routine treatment option in relapsed FL, none have demonstrated the potential for a cure [50]. Other key options at relapse include immunomodulators (R2, if not administered frontline) and PI3K inhibitors (such as idelalisib, copanlisib and duvelisib) [54] ( Table 1).…”
Section: Current Therapeutic Landscape For Lymphomamentioning
confidence: 99%